2014
DOI: 10.1007/s11356-014-3482-7
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cathepsin B activity by 2,3,7,8-tetrachlorodibenzo-p-dioxin

Abstract: 2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD) is the most potent toxic isomer in the dioxin-like family. Due to its resistance to metabolic degradation, this ubiquitous environmental pollutant readily accumulates in multiple organs. Cathepsin B is a lysosomal cysteine protease playing an essential role in the intracellular protein turnover. Alterations in its expression, activity, and localization may facilitate the development of many pathologies, including cancer. TCDD, due to its extremely lipophilic nature, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…increased amounts of lysosomal bodies with strong acid phosphatase activity which prevented T 4 disconnection from thyroglobulin (Collins et al, 1977). Moreover, both in vivo (Pocar et al, 2006) and in vitro experiments (Kędzior et al, 2015) revealed that dioxin and PCBs downregulate the mRNA expression and activity of cathepsin B, the enzyme responsible for solubilization of thyroglobulin and subsequent thyroid hormone liberation (Friedrichs et al, 2003). These assumptions, however, need further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…increased amounts of lysosomal bodies with strong acid phosphatase activity which prevented T 4 disconnection from thyroglobulin (Collins et al, 1977). Moreover, both in vivo (Pocar et al, 2006) and in vitro experiments (Kędzior et al, 2015) revealed that dioxin and PCBs downregulate the mRNA expression and activity of cathepsin B, the enzyme responsible for solubilization of thyroglobulin and subsequent thyroid hormone liberation (Friedrichs et al, 2003). These assumptions, however, need further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Our own studies have shown the significant effect that mechlorethamine and 2,3,7,8-tetrachlorodibenzo- p -dioxin (TCDD) have on hepatic metabolism [ 4 , 5 , 6 ]. In vitro studies have shown that these compounds interfere with the enzyme kinetics of cathepsin b, as well as having the ability to penetrate into lysosomes [ 7 ]. The negative effects of dioxins on hepatic metabolism were manifested by the increased frequency and severity of Disseminated Intravascular Coagulation (DIC) in induced pleurisy [ 8 ].…”
Section: Introductionmentioning
confidence: 99%